Replication properties of a contemporary Zika virus from West Africa. - Dana Machmouchi; Marie-Pierre Courageot; Chaker El-Kalamouni; Alain Kohl; Philippe Desprès (Public Library of Science (PLoS), 2024)
Zika virus (ZIKV) has become a global health problem over the past decade due to the extension of the geographic distribution of the Asian/American genotype. Recent epidemics of Asian/American ZIKV have been associated with developmental disorders in humans. There is mounting evidence that African ZIKV may be associated with increased fetal pathogenicity necessitating to pay a greater attention towards currently circulating viral strains in sub-Saharan Africa. Here, we generated an infectious molecular clone GUINEA-18 of a recently transmitted human ZIKV isolate from West Africa, ZIKV-15555. The available infectious molecular clone MR766MC of historical African ZIKV strain MR766-NIID was used for a molecular clone-based comparative study. Viral clones GUINEA-18 and MR766MC were compared for their ability to replicate in VeroE6, A549 and HCM3 cell lines. There was a lower replication rate for GUINEA-18 associated with weaker cytotoxicity and reduced innate immune system activation compared with MR766MC. Analysis of chimeric viruses between viral clones stressed the importance of NS1 to NS4B proteins, with a particular focus of NS4B on GUINEA-18 replicative properties. ZIKV has developed strategies to prevent cytoplasmic stress granule formation which occurs in response to virus infection. GUINEA-18 was greatly efficient in inhibiting stress granule assembly in A549 cells subjected to a physiological stressor, with NS1 to NS4B proteins also being critical in this process. The impact of these GUINEA-18 proteins on viral replicative abilities and host-cell responses to viral infection raises the question of the role of nonstructural proteins in the pathogenicity of currently circulating ZIKV in sub-Saharan Africa.